Systematic Review of Dimensions and Indicators in Sustainable and Smart Cities: Trends, Interdependencies, and Continental Variations - Roger Alejandro Parra-Pulido; Yolanda Teresa Hernández-Peña; Carlos Alfonso Zafra-Mejía (Urban Science)
Accelerated urbanization challenges cities globally. Ensuring good quality of life and environmental protection requires innovative, data-driven solutions. Sustainable and smart cities (SSCs) offer a promising response, but effective implementation depends on selecting and using appropriate dimensions and indicators. The main objective of this article is to present a systematic review within the framework of SSCs to study trends in the use of dimensions and indicators. A citation frequency index (Q) considering quartiles is used to determine the importance of the variables considered in this study. A spatiotemporal analysis of the dimensions and indicators detected is also performed. The results suggest that the multifaceted nature of SSCs necessitates a holistic approach, with environmental (Q3 = 0.536) and social (Q2 = 0.403) dimensions being principal. Despite the lower ranking (Q1 = 0.080) of the information and communication technology (ICT) dimension, its pervasive influence highlights its evolving importance. Effective ICT implementation relies on robust social and environmental foundations, illustrating their interdependence. The governance (Q1 = 0.169) dimension is also essential for the creation of transparent and equitable urban policies. Key indicators related to energy systems (Q2 = 0.379), data analysis (Q2 = 0.327), and resource management (Q2 = 0.291) are crucial for operational efficiency and sustainability. Continental differences in prioritizing SSC dimensions highlight the importance of context-specific strategies, reflecting unique challenges and opportunities faced by different continental areas. By understanding and addressing these continental differences, policymakers and urban planners can more effectively promote sustainable and resilient urban development worldwide.